Discretionary leniency and typological guilt: results from a Danish study of police discretion - Holmberg, Lars (Journal of Scandinavian studies in criminology and crime prevention, 2000)
Results from a qualitative study of police discretion in Denmark are presented. The aim of the study was to investigate the background for police decisions made on the spot, and to determine whether or not police discretion amounts to discrimination. Police discretion is analysed as two distinct forms of power, namely the power of definition/suspicion and the power of procedure/prosecution. The study shows that both forms are used in a discriminatory way, and it is argued that use of the power of suspicion results in discrimination. The power of prosecution, on the other hand, need not necessarily entail discrimination, but in practice it often does. The police discern between ?typical offenders' and ?decent citizens' and treat suspects differently according to type. The reason for this discrimination, it is argued, can be found in officers' notions of typological guilt , a form of ? alleged figuilt that is independent of concrete evidence. Differences in the degree of leniency experienced by different types of suspect can be interpreted as vicarious punishment of the typologically guilty. The impact of this kind of police practice on police?citizen relations, and possibilities for improvement, are discussed